Removal of copper from nickel anode electrolyte through ion exchange - 陈爱良 邱冠周 赵中伟 孙培梅 余润兰 (Transactions of Nonferrous Metals Society of China, 2009)
An novel method for removal of copper from nickel anodic electrolyte through ion exchange was studied after cupric deoxidization. Orthogonal design experiments show the optimum conditions of deoxidizing cupric into Cu＋ in the nickel electrolyte are the reductive agent dosage is 4.5 times as the theoretic dosage and reaction time is 0.5 h at 40℃ and pH 2.0. Ion exchange experiments show that the breakthrough capacity（Y） decreases with the increase of the linear flow rate（X）： Y=1.559-0.194X＋ 0.006 7X2. Breakthrough capacity increases with the increase of the ratio of height to radius（RRH）. The higher the initial copper concentration, the less the breakthrough capacity（BC）. SO42- and nickel concentration have no obvious change during the process of sorption, so it is not necessary to worry about the loss of nickel during the sorption process. Desorption experiments show that copper desorption from the resin is made perfectly with NaCl solution added with 4% （volume fraction） H2O2 （30%） and more than 100 g/L CuCl2 solution is achieved.